Land, labour and population in the industrial revolution. Essays presented to J.D. Chambers. Ed. by E.L. Jones & G.E. Mingay. [With contribs of G.E. Mingay, A.H. John, E.L. Jones a.o.] (Arnold, 1967)
With graphs, index, map, prt and tabs.